Anatomy of a duchy : the political and ecclesiastical structures of early Přemyslid Bohemia - Kalhous, David (East Central and Eastern Europe in the Middle Ages, 450-1450, 2012)
In Anatomy of a Duchy David Kalhous analyses military, social and "ideological" factors which may have led to the stabilisation of the P?emyslid regnum in 10th and 11 th century.